HR functions and their impact on job performance Survey study on public universities - األسخاذ امدكخِر َِشٔار وػروف كاكٍ وال; امىدرس امىساغد ةڕوا سٍردار أضىد (QALAAI ZANIST JOURNAL, 2018)
This study focuses on the human resources management strategies represented by (analysis strategy, planning strategy, recruitment strategy, training strategy, motivation strategy, performance appraisal strategy, occupational health and safety strategy) and their impact on improving the organizational performance represented by its dimensions of (completing assignments, discipline, quantity of work, and quality of work). The governmental universities have been selected to be statistically the population of this study along with testing study hypotheses of ten governmental universities by taking the views of managers totaling of (254). The problem study addresses a set of questions that includes:  Is there is an impact of human resources management strategies on improving the level of organizational performance for employees in the governmental universities in Iraqi Kurdistan region?  What are the managers perceptions about human resources strategies in the governmental universities in Iraqi Kurdistan region? This study aims to determine the human resources management strategies and their impact on improving the organizational performance of government universities in Iraqi Kurdistan region. To achieve the objectives of this study two main hypotheses have been adopted, drives from the first hypotheses seven sub hypotheses to verify the impact of human resource management strategies on improving the organizational performance. In order to prove that a survey questionnaire prepared comprises of 74 items. This study depended on the descriptive analytical method as well as used Statistical Package for Social Sciences software (SPSS V.20) inorder to analysis data. The study achieved a set of findings, including: 1. The managers' perceptions about the functions of human resources management in the govermental universities in Iraqi Kurdistan region came at a medium degree. 2. The managers' perceptions about the organizational performance in the govermental universities in Iraqi Kurdistan region came at a high degree. 3. Statistically there is a significant impact at the level of significance )α ≤ 0.05(of human resource management strategies in combined shape (human resource analysis strategy, human resource planning strategy, recruitment strategy, training and development strategy, motivation strategy, performance appraisal strategy, occupational health and safety strategy) on improving the organizational performance its dimensions include (completing assignments, discipline, quantity of work, and quality of work). Based on the findings, the study recommended the followings: 1. It is necessary for the considered universities to increase to activate human resource management functions in a manner that helps them to improve the level of employees performance, by monitoring the implementation of the plan in accordance to those strategies starting with workforce budgets and recruitment techniques, training courses, motivation systems, and so on. 2. The universities that have been studied should establish effective recruitment programs to attract the best human skills in the labor market through depending on people with scientific, technological and managerial qualifications in addition to intensify contacts using all electronic media and networks available. 3. The universities that have been studied should focus on the identification process of training needs , based on scientific criteria and most effective education systems analysis.